Análisis biogeográfico de la distribución conocida y potencial de cuatro taxa del género Prosopis L. (Leguminosae-Mimosoideae) en México - Ramírez Martínez, Azucena (Universidad Autónoma Metropolitana, 2015)
In Mexico, Prosopis has been studied mainly from the taxonomical, biological, ecological and cultural perspectives; whereas its distribution is limited to regional-geographic and floristic studies, restricting its biogeographic knowledge. The objectives of this study were to i) Determine the current and potential distribution of four taxa of Prosopis: P. glandulosa Torr. var. glandulosa, P. glandulosa var. torreyana (L.D. Benson) M.C. Johnst., P. juliflora (Sw.) DC., and P. laevigata (Humb. & Bonpl. ex Willd.) M.C. Johnst., and ii) Analyze their biogeography to identify their possible routes of dispersion in Mexico. The information obtained from biological collections (herbarium) and databases, was depurated and validated to obtain a final database with 585 records. Current distribution was obtained using ArcMap, while the potential distribution was modeled using MaxEnt algorithm, and the 19 climate layers for current-time and Middle Holocene obtained from WorldClim. Using ArcMap, the potential distribution maps were multiplied to obtain area relationships among taxa. A bioclimatic profile of each taxon was obtained using WorldClim layers, as well as layers of climate-and-vegetation from Mexico. The climate layers that best determined the potential distribution of each taxon were selected with the Jacknife Index and r-Pearson correlations. Current and potential distributions revealed that P. glandulosa var. glandulosa and P. glandulosa var. torreyana are located in the Mexican Plateau, and P. juliflora occurs in the Pacific Coast; whereas P. laevigata occurs from the Southern Plateau to the Valley of TehuacanCuicatlan. The distribution of P. juliflora was mostly defined by variables of precipitation; whilst the variables associated to temperature explained the distribution of the other taxa. Mean temperature and precipitation for each taxon were: 18°C and 394 mm to P. glandulosa var. glandulosa; 19°C and 324 mm to P. glandulosa var. torreyana; 27°C and 912 mm to P. juliflora, and 19°C and 568 mm to P. laevigata. An alelopatry between both varieties of P. glandulosa and P. laevigata, was detected in the Southern Plateau; whilst, in the Northern Plateau, both varieties of P. glandulosa, presented homopatry. In Baja California, P. glandulosa var. torreyana and P. juliflora showed a parapatry, and an alelopatry in the Sonorense Province. P. glandulosa var. torreyana, P. juliflora, and P. laevigata presented a possible area of coincidence in the Oaxaca province. Likewise, both the potential area to the present and the one shown in the Middle Holocene, indicated two possible dispersion routes from the Tehuantepec Isthmus: i) Towards the Center and the North of Mexico, and ii) Through the Pacific Coast to Southern Sonora and Baja California. The model for the Middle Holocene, supports the hypothesis that the four taxa could have dispersed, from the South to the North of Mexico, and that the first dispersion route, here proposed, explains the distribution of three of the four taxa studied. Key words: Biogeography, Dispersion, Distribution models, Legumes, Mesquites.; En México, Prosopis se ha estudiado esencialmente desde una perspectiva taxonómica, biológica, ecológica y cultural; pero el conocimiento de su distribución es limitado, ya que solo se ha documentado a través de estudios florísticos, geográficos regionales y, prácticamente, se desconoce su historia biogeográfica en el país. Los objetivos de este estudio fueron i) Determinar la distribución conocida y potencial de cuatro taxa de Prosopis: P. glandulosa Torr. var. glandulosa., P. glandulosa Torr. var. torreyana (L.D. Benson) M.C. Johnst., P. juliflora (Sw.) DC., y P. laevigata (Humb. & Bonpl. ex Willd.) M.C. Johnst., y ii) Realizar un análisis biogeográfico y reconocer las posibles rutas de su dispersión en México. Se depuró y validó la información obtenida de colecciones (herbarios) y bases de datos biológicos, para conformar una base de datos final con 585 registros. Para cada taxon, se obtuvo la distribución conocida con ArcMap, y se modeló su distribución potencial con el algoritmo MaxEnt y las 19 coberturas climáticas de WorldClim, tanto actuales como al Holoceno Medio. Mediante ArcMap se realizó la multiplicación de los mapas de distribución potencial para detectar relaciones de área entre los taxa. Se elaboró el perfil bioclimático de cada taxon a partir de las 19 coberturas de WorldClim, y de las de clima y vegetación para México. Mediante el índice de Jacknife y correlaciones de r-Pearson, se seleccionaron las variables climáticas que mejor determinan la distribución potencial de cada taxon. La distribución conocida y potencial reveló que P. glandulosa var. glandulosa y P. glandulosa var. torreyana, se localizan en el Altiplano Norte y Sur, P. juliflora en la Costa del Pacífico; mientras que P. laevigata se distribuye desde el Altiplano Sur hasta el Valle de Tehuacán-Cuicatlán La distribución de P. juliflora fue definida mayormente por variables de precipitación; mientras que las variables asociadas a la temperatura determinaron la distribución de los otros tres taxa. La temperatura y precipitación promedio para los taxa fueron: 18°C y 394 mm para P. glandulosa var. glandulosa; 19°C y 324 mm para P. glandulosa var. torreyana; 27°C y 912 mm para P. juliflora; 19°C y 568 mm en el caso de P. laevigata. En el Altiplano Sur, se detectó alelopatría entre ambas variedades de P. glandulosa y P. laevigata, pero en el Altiplano Norte, ambas variedades de P. glandulosa, presentaron homopatría. Entre P. glandulosa var. torreyana y P. juliflora se detectó parapatría en Baja California, y alelopatría en la Provincia Sonorense. P. glandulosa var. torreyana, P. juliflora y P. laevigata, presentaron una área probable de coincidencia en la provincia de Oaxaca. Por su parte, el área potencial en el presente y al Holoceno Medio indicó dos probables rutas para su dispersión a partir del Istmo de Tehuantepec: i) Hacia el Centro y Norte del país, y ii) Por la Costa del Pacífico hasta el Sur de Sonora y Baja California. Asimismo, la modelación al Holoceno Medio, apoya la hipótesis de que, al menos, los cuatro taxa pudieron dispersarse, de Sur a Norte en México y que la primera ruta de dispersión, explica la distribución de tres de los cuatro taxa estudiados. Palabras clave: Biogeografía, Dispersión, Leguminosas, Mezquites, Modelos de Distribución.